Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.2 - Addition and Subtraction of Rational Numbers - Problem Set 2.2 - Page 58: 91



Work Step by Step

We first apply the distributive property. Then, we simplify the resultant expression: $-n-\frac{7}{9}n-\frac{5}{12}n$ =$n(-1-\frac{7}{9}-\frac{5}{12})$ =$n(\frac{-1(36)-7(4)-5(3)}{36})$ =$n(\frac{-36-28-15}{36})$ =$n(\frac{-36-43}{36})$ =$n(\frac{-79}{36})$ =$-\frac{79}{36}n$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.